2022
DOI: 10.3389/fgene.2022.897696
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in the Breeding of Common Bean Through a Combined Approach of in vitro Regeneration and Machine Learning Algorithms

Abstract: Common bean is considered a recalcitrant crop for in vitro regeneration and needs a repeatable and efficient in vitro regeneration protocol for its improvement through biotechnological approaches. In this study, the establishment of efficient and reproducible in vitro regeneration followed by predicting and optimizing through machine learning (ML) models, such as artificial neural network algorithms, was performed. Mature embryos of common bean were pretreated with 5, 10, and 20 mg/L benzylaminopurine (BAP) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…Using ML algorithms to predict and analyze tissue culture systems are promising to optimize in vitro culture procedures [ 18 , 22 , 86 ]. The application of different ANNs is an active area of research in tissue culture [ 18 ] which has been used in different systems of in vitro culture such as callogenesis [ 20 ], shoot proliferation [ 46 ], androgenesis [ 44 ], somatic embryogenesis [ 36 ], and direct shoot regeneration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using ML algorithms to predict and analyze tissue culture systems are promising to optimize in vitro culture procedures [ 18 , 22 , 86 ]. The application of different ANNs is an active area of research in tissue culture [ 18 ] which has been used in different systems of in vitro culture such as callogenesis [ 20 ], shoot proliferation [ 46 ], androgenesis [ 44 ], somatic embryogenesis [ 36 ], and direct shoot regeneration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data quality, the sample of data collected from the domain, and model fit are the three important sources of uncertainty in ML studies [ 44 ]. Several researchers have recommended the application of different machine learning to tackle uncertainty issues [ 29 , 43 , 60 , 63 ]. Therefore, three neural network approaches (MLP, RBF, and GRNN) were employed for modeling contamination rate and seed germination percentage on in vitro seed sterilization and germination of petunia.…”
Section: Discussionmentioning
confidence: 99%
“…Simplicity of network structure, very fast network training speed, strong non-linear mapping capability, ease of implementation, high fault tolerance, and high robustness in the solution of complex problems are excellent features of GRNN [ 50 ]. Recent studies have reported the good performance and superior predictive accuracy of ANNs tools over traditional statistics for predicting and optimizing in vitro culture systems of different plant species such as chrysanthemum [ 35 , 51 54 ], passion fruit [ 50 ], Prunus rootstock [ 55 57 ], tomato [ 58 ], chickpea [ 59 , 60 ], wheat [ 49 ], cannabis [ 28 , 29 , 61 64 ], and ajowan [ 65 ]. In addition, the combination of ANNs with an evolutionary optimization algorithm as a superior and reliable computational method confers advantages to predict critical factors that impact plant growth parameters in in vitro culture systems [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…While recent advances in plant-culture regeneration, gene-editing, and machine learning technologies [44] are expected to tackle the bottlenecks associated with transformation and regeneration procedures for the recalcitrant crops. In the meantime, transitory or chimeric transformation meditated by R. rhizogenes combined with CRISPR/Cas9 system has been proven as an excellent technique to generate gene-edited hairy roots 41• , 45 .…”
Section: Application Of Metabolomic Analysis Of Clustered Regularly I...mentioning
confidence: 99%